Foreign Currency Deposits and the Demand for Money in Developing Countries - Khan, Mohsin (IMF Working Papers; Working Paper, 1992)
This paper examines the relative demands for domestic and foreign currency deposits by residents of developing countries. A dynamic currency substitution model that incorporates forward-looking rational expectations is formulated and then estimated for a group of ten developing countries. The results indicate that the foreign rate of interest and the expected rate of depreciation of the parallel market exchange rate are important factors in the choice between holding domestic money or switching to foreign currency deposits held abroad. From an empirical standpoint, the forward-looking framework adopted here also turns out to be superior to the conventional currency-substitution model.